Wpływ absorpcji środków unijnych na potencjał finansowy gmin województwa lubelskiego w latach 2004-2005 - Miszczuk, Magdalena (The Influence of the Absorption of the EU Funds on the Financial Potential of the Lublin Region's Gminas between 2004 and 2005, 2008)
The author analyzes the way in which the raising of the EU funds influences the increase of the financial potential of the gminas of the Lublin region. In order to do that the author has taken a look at the share foreign funds in the budgetary income and expenditure. To present the results of the analysis a typology was created which reflects their income and expenditure and the share of foreign funds. The analysis of the data has proved that on average the increase of the financial potential of the local self-governments of the Lublin region has not been considerable. In 2005 the share of foreign funds in the income was higher than in the expenditure, which means that in the future there will be an increase trend of the financial potential because of the absorption of the EU funds. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 3, s. 451-460